What is the appropriate management of iron deficiency in young children?. Issue 10 (October 2015) - Allen, Thomas W.; Ivins, Douglas; Petsas, Kristina; Chung, Jason
Abstract : Evidence‐Based Answer : Iron supplementation improves hemoglobin and ferritin levels in anemic and nonanemic iron deficiency (SOR: C, disease‐oriented outcomes). There appears to be an increase in cognitive scores, height, and weight in anemic children, but not in nonanemic children with iron deficiency (SOR: B, systematic reviews with inconsistent results). Giving oral ferrous sulfate once a day is as effective as splitting the dose and giving TID (SOR: B, RCT).